Harmonizing the National Curriculum and Islamic Values: A Study on Curriculum Development in Islamic Junior High Schools - M. Qaimul Adel El Hakiemy; Hasnah Luthfiyah; Kalayo Hasibuan (English Education Study Program Faculty of Teacher Training and Education, 2025)
Curriculum development in Islamic education institutions at the junior high school level is a crucial process that ensures the alignment of educational practices with Islamic values and contemporary educational standards. This study examines the roles of teachers, challenges, and strategies in curriculum development as highlighted in various studies, including the integration of Islamic boarding school programs, principles of Islamic education curriculum design, and comparisons with international practices. The research also explores the management aspects and competitive strategies for enhancing the quality of Islamic education. The findings provide comprehensive insights into effective curriculum development for Islamic education in junior high schools, emphasizing adaptability, integration, and stakeholder collaboration.